1968
DOI: 10.4098/at.arch.68-18
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the proposed international biological program census method for estimating small mammal populations

Abstract: Polish workers have proposed a method of estimating small rodent populations based on removal trapping. Using a linear regression method, they obtained reliable population estimates with five days of prebaiting followed by five days of removal trapping. The aim of our study was to compare the results obtained, using the same method at the Atomic Energy Commission's Savannah River Plant in the Southeastern United States, with the results of the Polish investigators. Our study area consisted of 5.8 ha over which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

1969
1969
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 4 publications
1
33
0
1
Order By: Relevance
“…Large variations in P c for given species over the first few nights means that no population estimate can be obtained (e.g. Gentry et al, 1968). Hayne (1949) did not give r values in his original paper and our recalculations of his data indicate a nonsignificant fit of his data to his model for the example.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Large variations in P c for given species over the first few nights means that no population estimate can be obtained (e.g. Gentry et al, 1968). Hayne (1949) did not give r values in his original paper and our recalculations of his data indicate a nonsignificant fit of his data to his model for the example.…”
Section: Discussionmentioning
confidence: 90%
“…6 & 9). The Polish recommendation of five days of removal can result in an entirely erroneous picture of the mammal community (Gentry, et al 1968;Faust et al 1971;Kaufman, et al 1971). Another approach might be to develop techniques to measure the magnitude of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of a standard way to determine the density of small mammals (Grodziriski, Pucek & Ryszkowski, 1966) has been hampered by the fact that, during the first few days of removal trapping, some species of small mammals may be taken at very low rates relative to their actual abundance (Gentry, Golley& Smith, 1968. Calhoun (1959Calhoun ( , 1964 suggested that such lags in catch were due to community organization -the presence of a psychologically dominant species seems to inhibit the movements of some subordinate species, in effect preventing them from encountering traps until inhibitions are relased by the removal of the more dominant species.…”
Section: Introductionmentioning
confidence: 99%